Comparison of Larval and Adult Drosophila Astrocytes Reveals Stage-Specific Gene Expression Profiles. Issue 4 (1st April 2015) - Huang, Yanmei; Ng, Fanny S; Jackson, F Rob
Abstract: The analysis of adult astrocyte glial cells has revealed a remarkable heterogeneity with regard to morphology, molecular signature, and physiology. A key question in glial biology is how such heterogeneity arises during brain development. One approach to this question is to identify genes with differential astrocyte expression during development; certain genes expressed later in neural development may contribute to astrocyte differentiation. We have utilized the Drosophila model and Translating Ribosome Affinity Purification (TRAP)-RNA-seq methods to derive the genome-wide expression profile of Drosophila larval astrocyte-like cells (hereafter referred to as astrocytes) for the first time. These studies identified hundreds of larval astrocyte-enriched genes that encode proteins important for metabolism, energy production, and protein synthesis, consistent with the known role of astrocytes in the metabolic support of neurons. Comparison of the larval profile with that observed for adults has identified genes with astrocyte-enriched expression specific to adulthood. These include genes important for metabolism and energy production, translation, chromatin modification, protein glycosylation, neuropeptide signaling, immune responses, vesicle-mediated trafficking or secretion, and the regulation of behavior. Among these functional classes, the expression of genes important for chromatin modification and vesicle-mediated trafficking or secretion is overrepresented in adult astrocytes based on Gene Ontology analysis. Certain genes with selective adult enrichment may mediate functions specific to this stage or may be important for the differentiation or maintenance of adult astrocytes, with the latter perhaps contributing to population heterogeneity.